SPATIAL MEMORY ACTIVITY IN ETHYL ACETATE FRACTION OF MENIRAN MERAH (PHYLLANTHUS URINARIA L.) WITH RADIAL ARM MAZE METHOD - Karunita Ika Astuti (Borneo Journal of Pharmascientech, 2019)
ABSTRACT Intelligence is an ability to adjust with the environment by blends of attention, concentration and short term memory. Phyllanthus urinary L. is a plant that have active content of flavonoid compound especially quersetin which efficacious in spatial memory activity. The purpose of this study was to determine, effective dose and histopathology of gyrus dentatus in animal test after given ethyl acetate fraction of meniran herb. The research was conducted by administration of ethyl acetate fraction with doses 50 mg/kgBW, 100 mg/kgBW and 150 mg/kgBW for 10 days to white male mice. The research to view error in memory by radial arm maze (RAM). Positive control using quercetin 42 mg/kg BW and negative control using Na-CMC 0.5%. The most effective result at dose 100 mg/kgBW with shows value of 38.619% ± 2.56, the best and smaller value if compared with 50 mg/kgBW and 100 mg/KgBW and negative control, 49.195%±4.27; 53.130%±1.70; and 63.419%±4.55, respectively with positive control value of 32.424%±9.13. Keywords: Radial arm maze, ethyl acetate fraction, red meniran (Phyllanthus urinary L.)